2008
DOI: 10.1111/j.1728-4465.2008.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐related School Dropout and Prior School Performance in KwaZulu‐Natal, South Africa

Abstract: This study uses data from KwaZulu-Natal, South Africa, to examine the factors associated with schoolgirl pregnancy and subsequent educational pathways. We find that prior schooling discontinuities--defined as instances of non-pregnancy-related grade repetition or temporary withdrawals from school--are strongly associated with a young woman's likelihood of later becoming pregnant while enrolled in school, dropping out of school if she becomes pregnant, and not returning to school following a pregnancy-related d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
134
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 23 publications
9
134
2
5
Order By: Relevance
“…While research in a variety of cultural settings indicates that premarital pregnancy can be a leading cause of early motherhood in impoverished communities, this is not the dominant pattern for young mothers in Lombok (Biddlecom et al 2008;Grant and Hallman 2008). Conservative sexual norms and constant social surveillance of women prior to marriage mean that the majority of young Sasak women will be married when they fall pregnant with their first child, and virtually all will be married before the child's birth.…”
Section: Why Marry Early?mentioning
confidence: 99%
“…While research in a variety of cultural settings indicates that premarital pregnancy can be a leading cause of early motherhood in impoverished communities, this is not the dominant pattern for young mothers in Lombok (Biddlecom et al 2008;Grant and Hallman 2008). Conservative sexual norms and constant social surveillance of women prior to marriage mean that the majority of young Sasak women will be married when they fall pregnant with their first child, and virtually all will be married before the child's birth.…”
Section: Why Marry Early?mentioning
confidence: 99%
“…In lowincome countries, pregnancy is one of the main causes of school dropout among schoolgirls [29] and affects women's future income as well as the nation's human capital. Net cost of children is defined as the present value of expected outlays plus the imputed value of the parents' services, minus the present value of the expected money return, plus the imputed value of the child's services [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research has shown that teenage parenthood is a marker for social disadvantage (National Campaign, 2010). Although teenage birth rates in the United States were shown to steadily reduce between 1991 and 2006, there have been increases in the number of teenage mothers of age 15 to 19 years (Goyder, Blank & Peters, 2003;Grant & Hallman, 2008). Available statistics reveal that three in 10 girls become pregnant by age 20 years, with over 750000 teen pregnancies annually (National campaign, 2010).…”
Section: Introductionmentioning
confidence: 99%